2007
DOI: 10.5511/plantbiotechnology.24.335
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of basic helix-loop-helix proteins, AtPTF1 and NtWIN4, with reference to plastid localization

Abstract: Basic helix-loop-helix (bHLH) proteins constitute one of the most abundant types of transcription factor in both plants and animals. They are considered to be localized in the nucleus, but recent surveys have revealed two exceptions, NtWIN4 from tobacco and AtPTF1 from Arabidopsis, both reported to localize to plastids. Their specific subcellular localization was suggested to be the result of structural change, whose analysis might provide clues to understanding protein evolution. Consequently we performed com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The finding that light-dependent psbD transcription was not diminished in ptf1 mutants suggests that PTF1 is unlikely to be involved in light signaling (Tsunoyama et al 2004). We also established a GFP-tagged PTF1 to be clearly localized only in nuclei, and not in plastids (Kodama and Sano 2007), and that it exhibited repression activity on nuclear transcription by dualluciferase assay (Kodama and Sano 2007). These observations suggest that PTF1 be carefully reevaluated as to biological functions and cellular localization in future.…”
Section: Ptf1mentioning
confidence: 75%
“…The finding that light-dependent psbD transcription was not diminished in ptf1 mutants suggests that PTF1 is unlikely to be involved in light signaling (Tsunoyama et al 2004). We also established a GFP-tagged PTF1 to be clearly localized only in nuclei, and not in plastids (Kodama and Sano 2007), and that it exhibited repression activity on nuclear transcription by dualluciferase assay (Kodama and Sano 2007). These observations suggest that PTF1 be carefully reevaluated as to biological functions and cellular localization in future.…”
Section: Ptf1mentioning
confidence: 75%
“…The NtWIN4 protein, a bHLH motif containing a wound-induced protein from N. tabacum , has also been reported to be a transcription repressor with roles in adaption to biotic and abiotic stresses ( Kodama and Sano, 2006 ). Kodama and Sano (2007) suggested that these proteins have evolved from eukaryotic nuclear transcription factors into plastid functional proteins. Furthermore, a current hypothesis is that these genes were altered evolutionarily to allow plants to cope with environmental stresses ( Sato, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genome of Arabidopsis thaliana has been shown to contain as many as 147 genes encoding bHLH proteins, these apparently constituting the largest nuclear transcription factor family [24,25]. In our previous studies, we found a novel bHLH protein from N. tabacum, designated as NtWIN4 (N. tabacum wound-induced clone 4), localized in chloroplasts [19,26,27]. Functional and structural analyses indicated involvement of NtWIN4 in stress responses, and indicated that it has been converted from a nuclear Abbreviations used: bHLH, basic helix-loop-helix; BY2, bright yellow 2; GFP, green fluorescent protein; NsWIN4, Nicotiana sylvestris wound-induced clone 4; NtWIN4, Nicotiana tabacum wound-induced clone 4; 5 -RACE, 5 -rapid amplification of cDNA ends; RT, reverse transcriptase; UTR, untranslated region.…”
Section: Introductionmentioning
confidence: 96%